The Digital Frontier: Can Artificial Intelligence Detect Parkinson's Disease? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2024)
Parkinson's disease PD is a progressive neurodegenerative disorder that affects millions globally. Its insidious onset and the challenge of accurate early di...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Medical Ethics